Translation of humour in the English subtitles of two Malaysian Chinese films / Tu Kah Yee - Tu , Kah Yee (2020)
This study attempts to investigate humour translation in two Malaysian Chinese New Year films: Woohoo! and The Journey. There are two objectives of this study: i) to find out the translation strategies used in subtitling humour into English subtitles, and ii) to analyse whether the humour in the films is effectively translated into English subtitles. Chiaro’s (2010) strategies for subtitling verbally expressed humour (VEH) are adopted to analyse the strategies employed in subtitling humour. The results of the study show that leaving the humour unchanged and ignoring the humour are the two most common strategies used in subtitling humour in the selected films. Moreover, it is found that for some humorous instances, a combination of strategies is used to translate the humour. The findings also reveal that some subtitling strategies are more commonly used in translating certain types of humour. To answer the second research question, Martínez_Sierra’s (2006) methodology is adopted to investigate the effectiveness of the translation of humour by analysing the humorous elements found in the source language and the target language. The findings show that humorous elements are preserved, changed or lost in the English subtitles. In addition, the findings reveal that humour that is generated based on linguistic elements is the most difficult type to translate.